Clinical Effectiveness of High-Intensity Laser in Wound Management: A Systematic Review and Meta-Analysis - Jeanette R.A. Leo; David S. Perdanakusuma; Ardea Perdanakusuma; Natalia Wahyudi (International Journal Labs, 2026)
Chronic wounds remain a major healthcare challenge because of their prolonged healing time, increased risk of infection, extended hospitalization, reduced quality of life, and substantial healthcare costs. High-Intensity Laser Therapy (HILT) has emerged as a promising noninvasive intervention that may enhance wound healing by stimulating tissue regeneration, improving microcirculation, promoting collagen synthesis, and accelerating wound closure. This systematic review and meta-analysis aimed to evaluate the efficacy of HILT compared with conventional wound care, standard medical treatment, or sham laser therapy in improving wound-healing outcomes among patients with chronic and delayed-healing wounds. A systematic literature search was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the PubMed, Scopus, ScienceDirect, and Google Scholar databases up to May 2026. Eligible studies were selected based on predefined inclusion and exclusion criteria. The methodological quality of the included studies was assessed using the Jadad Scale. Five interventional studies met the eligibility criteria and were included in the systematic review. Of these, three studies provided sufficiently homogeneous quantitative data and were included in the meta-analysis. The pooled analysis demonstrated that HILT significantly reduced wound surface area compared with control interventions (mean difference = ?3.53; 95% confidence interval: ?5.66 to ?1.40; p = 0.001), although substantial heterogeneity was observed among the studies (I² = 96%). In addition, the included studies consistently reported improvements in wound size reduction, wound appearance, wound-healing scores, and overall clinical outcomes following HILT.